Dose, benefit, and risk in medical imaging - Dauer, Lawrence (Boca Raton, Florida : CRC Press, 2019)
This timely overview of dose, benefit, and risk in medical imaging explains to readers how to apply this information for informed decision-making that improves patient outcomes. The chapters cover patient and physician perspectives, referral guidelines, appropriateness criteria, and quantifying medical imaging benefits. The authors have included essential discussion about radiologic physics in medical imaging, fundamentals of dose and image quality, risk assessment, and techniques for optimization and dose reduction. The book highlights practical implementation aspects with useful case studies and checklists for treatment planning. Clinicians, students, residents, and professionals in medical physics, biomedical engineering, radiology, oncology, and allied disciplines will find this book an essential resource with the following key features: Discusses risk, benefit, dose optimization, safety, regulation, radiological protection, and shared & informed decision-making. Covers regulatory oversight by government agencies, manufacturers, and societies. Highlights best practices for improving patient safety and outcomes. Gives guidelines on doses associated with specific procedures.
OCLC-licensed vendor bibliographic record.
Keywords: Diagnostic imaging; Radiation -- Measurement; Diagnostic imaging -- Safety measures; Radiation dosimetry; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / Radiology & Nuclear Medicine; SCIENCE / Physics